PENDAMPINGAN DIGITAL MARKETING PADA UMKM SALOME NINGSIH SEBAGAI PENUNJANG KEGIATAN PROMOSI DAN PEMASARAN - Ita Purnama; Nur Fauziah Nabila; Desi Fitrianingsih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the growth of the Indonesian economy. At present, the development of technology and digitalization in various fields, MSMEs are a type of business that has a very large influence on economic development and also needs to experience progress in the field of technology, especially in marketing products. The purpose of this service is to develop MSMEs in terms of digital marketing and also expand the MSME marketing network. MSME Salome Ningsih is one example of an MSME that requires digital marketing assistance. The method used in community service activities is divided into three stages, namely the survey stage, digital marketing socialization, digital marketing assistance, and the maintenance and evaluation stage. The form of community service with the aim of developing and participating in digital marketing assistance for MSME Salome Ningsih so that it can have a marketing network that is not limited to the local market only.